Implementasi Light Emitting Diode Sebagai Penerangan Jalan Umum Yang Hemat Daya - Edy Sumarno; Juhana Juhana; Jan Setiawan (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Public street lighting, also known as street lighting, refers to the outdoor lighting systems used to illuminate public roads. An effective street lighting system plays a crucial role in enhancing safety and security for pedestrians, cyclists, and motorists by providing improved visibility of the road and surrounding terrain during nighttime hours. The primary focus in street lighting planning is on economic factors. An analysis of light sources has highlighted the economic advantages of utilizing light emitting diodes for public street lighting. This choice proves to be more efficient when implemented in a sustainable manner. The installation of public street lighting can be the optimal solution to address the issue of inadequate lighting in the village of Pedurenan Gunung Sindur Bogor, ensuring enhanced comfort and security during nighttime activities. The lighting installation process commences with a thorough examination of the site, followed by diligently arranging and design of the electrical installations for the lighting system. Finally, the planned design was carried out and implemented. The implementation of public street lighting is a collaborative effort between college students and youth residents in the village. The outcome of this community service initiative is the implementation of public street lighting installations that offer optimal illumination, ensuring the convenience and safety for all people accessing the roads.